PENGEMBANGAN PROSPEK USAHA TORTILLA CHIPS OLEH KELOMPOK TANI AUR SERUMPUN DI KECAMATAN SIMPANG ALAHAN MATI KABUPATEN PASAMAN PROVINSI SUMATERA BARAT - Daimon Syukri; Nika Rahma Yanti; Emil Salim; Ismed Ismed; Cesar Wellya Refdi; Felga Zulfia Rasiana; Wellyalina Wellyalina; Novizar Nazir; Aisman Aisman (LPPM Universitas Andalas, 2023)
The Aur Serumpun farmer group is one of the growing farmer groups with their corn farming business. This farmer group is in Simpang Alahan Mati District, Kab. Pasaman, West Sumatra Province. So far, farmers only sell corn that has been dried directly. The processing of corn is a basic need for members of farmer groups in order to have product diversification which can ultimately increase the economy of these farmers. In the community service activities that were carried out previously (in 2019), processed products from corn were introduced, namely tortilla chips. In the 2020-2022 activities, business development will be carried out from Aur Serumpun farmer groups in accordance with the policy directions set by the members of the farmer groups themselves. Therefore, a discussion group forum was held and the signing of a cooperation agreement regarding the study of the prospects for producing tortilla chips which would be carried out by the aur allied farmer groups. The development of food product production of trotilla chips is an independent initiative from farmer groups that can collaborate with academics in the Department of Agricultural Product Technology, Andalas University. It was agreed from the discussion group forum that the head of the farmer group would conduct a study and socialize to other members of the farmer group regarding alternative product diversification of the commonly produced corn commodity. Further evaluation of the prospects for the implementation of the tortilla chips production process will be carried out next year.